2003
DOI: 10.1063/1.1531820
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of electrical degradation and breakdown of insulating polymers

Abstract: The electrical breakdown of polymers with saturated bonds is considered as a consequence of formation of low-density regions in the bulk of the polymers. These regions form due to the dissociation of chemical bonds initiated by the ionization of macromolecules in a high electric field. It was shown that the electrical lifetime of a polymer can be estimated based on this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 22 publications
2
48
0
3
Order By: Relevance
“…As a rule, a correlation of the parameters of electric breakdown calculated according to the impact ionization model with the experimental results is rather poor. The discrepancy of the experimental and calculated results is especially dramatic for dynamics of breakdown, which impelled some investigators to look for alternative models of breakdown in amorphous semiconductors and dielectrics [1][2][3][4][5]. Earlier studies of non-equilibrium processes provided evidence of some cooperative effects in amorphous materials [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…As a rule, a correlation of the parameters of electric breakdown calculated according to the impact ionization model with the experimental results is rather poor. The discrepancy of the experimental and calculated results is especially dramatic for dynamics of breakdown, which impelled some investigators to look for alternative models of breakdown in amorphous semiconductors and dielectrics [1][2][3][4][5]. Earlier studies of non-equilibrium processes provided evidence of some cooperative effects in amorphous materials [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Several different mechanisms have been proposed including electronic, avalanche, electromechanical, thermal breakdowns, and partial discharges. 1 One of the important observations during breakdown studies is that the electrical breakdown strength of solid dielectrics has been found to decrease with the increase in sample thickness. An inverse power law is generally reported 2 …”
mentioning
confidence: 99%
“…Этот вывод находится в согласии с результатами изучения долговечности полимеров в постоянном электрическом поле [13,[19][20][21]. В обоих случаях (как в постоянном поле, так и в поле, напряженность которого возрастает со временем) долговечность определяется скоростью накопления повреждений макромолекул, т. е. скоростью их ионизации.…”
Section: экспериентальные данные и их обсуждениеunclassified